Predictors Associated With Knowledge and Practice of Helminthic Infection Prevention Among Rural School-Aged Children's Parents in Bangladesh: A Cross-Sectional Study - Md. Safaet Hossain Sujan; Md. Safaet Hossain Sujan; Md. Saiful Islam; Md. Saiful Islam; Shabnam Naher; Rajon Banik; David Gozal (Frontiers Media S.A., 2020)
Background: Parasitic infection has become a major public health concern in light of its increasing prevalence in developing countries, particularly in rural settings. Helminthic infections disproportionately affect children, and therefore appropriate parental knowledge and practical approaches to transmission prevention are essential. The objective of this study was to evaluate the level of knowledge and implementation measures aimed at preventing helminthic infection among rural school-aged children's parents in Bangladesh.Methods: A cross-sectional survey was conducted among the parents of 449 rural school-aged children residing in 17 villages of the Cumilla district in Bangladesh. Participants completed the survey examining socio-demographic variables as well as questions regarding knowledge and practice of helminthic infection prevention (HIP).Results: Local knowledge about children's HIP was inadequate among their parents (81.5%). Furthermore, actual implementation of HIP measures was poor (42.1%). Knowledge of HIP was significantly associated with parental religion, education, occupation, number of family members, family income, housing conditions, and sanitation system. In addition, practice of HIP was significantly associated with the aforementioned factors, as well as with water source and knowledge of HIP.Conclusion: Lack of concern about parasitic infection among children's parents and their untoward effects on children's health is pervasive in rural parental settings, along with ignorance on helminthic transmission and its prevention. Public education programs aimed at addressing these glaring HIP awareness deficits are needed in Bangladesh.